Systematic revision of the living African Slender-snouted Crocodiles (Mecistops Gray, 1844) - Shirley, Matthew H.; Carr, Amanda N.; Nestler, Jennifer H.; Vliet, Kent A.; Brochu, Christopher A. (Zootaxa, 2018)
Molecular and morphological evidence has shown that the African slender-snouted, or sharp-nosed, crocodile Mecistops cataphractus (Cuvier, 1824) is comprised of two superficially cryptic species: one endemic to West Africa and the other endemic to Central Africa. Our ability to characterize the two species is compromised by the complicated taxonomic history of the lineage and overlapping ranges of variation in distinguishing morphological features. The name M. cataphractus was evidently originally based on West African material, but the holotype is now lost. Although types exist for other names based on the West African form, the name M. cataphractus is sufficiently entrenched in the literature, and other names sufficiently obscure, to justify retypification. Here, we designate a neotype for M. cataphractus and restrict it to West Africa. We resurrect M. leptorhynchus as a valid species from Central Africa and identify exemplary referred specimens that, collectively, overcome the obscurity and diagnostic limits of the extant holotype. We additionally indicate suitable neotype material in the event the holotype is lost, destroyed, or otherwise needing replacement, and we rectify the previously erroneous type locality designation. We provide a revised diagnosis for crown Mecistops, and revise and update previous descriptions of the two living species, including providing both more complete descriptions and discussion of diagnostic characters. Finally, we provide considerable discussion of the current state of knowledge of these species’ ecology, natural history, and distribution.